Prevalencia de la dermatitis atópica en niños de 1 - 14 años de edad en el Hospital Regional Isidro Ayora de Loja, periodo enero-julio 2015. - Quiñonez Morocho, Maritza del Carmen (2016)
The Atopic Dermatitis is a disease of global distribution with a growth of prevalence in infants, children and adolescents by setting a very high index in developed countries, to what has become a priority for the health. The overall objective of this research is to assess the prevalence of atopic dermatitis in children 1-14 years of age in the Regional Hospital Isidro Ayora of the city of Loja in the period January - July 2015.It is a study of descriptive type. The present research work was conducted in a total of 5095 patients between 1-14 years old treated in the outpatient consultation area of the Regional Hospital Isidro Ayora of the city of Loja during the period January-July, through the implementation of a survey and collection of data from the clinical history in which included the age and gender thus establishing the prevalence of Atopic Dermatitis the same that turned out to be 1%. We were able to establish the existence of the atopic dermatitis in children 1-24 months (32%), 3-12 years (57%) this being the most relevant age group, 13-14 years (15%), whereas according to the genre the more prevalent was the female (54 %/) in relation to the male (46%). In conclusion the actual percentage of prevalence of atopic dermatitis in patients of 1-14 years attending the outpatient consultation is 1%. Key words: Atopic Dermatitis, prevalence